Exploring the Potential of Religious Literacy in Pakistani Education - Ashraf, Muhammad Azeem (Religions, 2019)
Religious education is a compulsory subject in Pakistani schools in which students learn basic knowledge about Islam without exploring the sectarian differences between each sect of Islam. The division of Muslims into Sunni and Shia and the further division of Sunni Muslims into different sects has caused massive sectarian violence in Pakistan. This study uses qualitative methods to explore the possibility of engaging with religious literacy and religious education to explain the purpose, contents, and practical application of religious education and to mitigate existing challenges linked to religion in Pakistan. Even though religious education does not support sectarian differences, individual opinions about sectarian differences are still a major component of divisiveness in Pakistani society. Through interviews with 25 teachers from different levels of education (six primary school teachers, five high school teachers, five college teachers, five university teachers, and four religious school teachers), in this article, I argue that teachers of religious education in schools are neither following a common faith in teaching religious education nor are they in full agreement on providing equal rights to all students of different religious beliefs. Rather, most believe in their personal ideology centered on their own particular religious sect that largely rejects the concept of religious literacy. There is a need for evaluation and improvement of the teaching and learning of religion in schools in order to explain misperceptions about its practical application as well as to engage religious education with diversity.